THE ACTIVITIES OF NON-ISLAMIC RELIGIOUS ORGANIZATIONS ON THE EXAMPLE OF FERGANA REGION IN TODAY - Jumaev Shokhruh Shukhratjon Ugli (Galaxy International Interdisciplinary Research Journal, 2021)
This article provides religious tolerance and interethnic harmony in Uzbekistan and legal guarantees of social protection of multi-ethnic citizens in the political life of the country, the penetration of Christianity in the territory of Fergana region, the construction of churches and their present-day activities are covered.